TIMING OF LARVAL RELEASE BY REEF CORAL Pocillopora damicornis AT PANJANG ISLAND, CENTRAL JAVA - Munasik, -; Suharsono, -; Situmorang, J.; Kamiso, H. N. (Marine Research in Indonesia, 2008)
Monthly larval release by the coral Pocillopora damicornis at Panjang Island, Central Java was investigated. Corals were collected from windward and leeward and maintained in outdoor, flow-trough system to quantify nightly release of larvae. Larval release of the coral occurs every month throughout the year, and its planulation increased during dry monsoon. Monthly planulation occurs from new moon to full moon and possesses in different pattern between single and paired colonies. Planulation in paired colonies occurred in single peak and more synchronized in each colony however single colonies planulated in double peaks and less synchronized in each colony. This study confirmed that planulation period of P. damicornis at Panjang Island over a range of lunar phases with shorter periods of peak release which predominantly controlling by tidal range rather than lunar cycle.